The factors impacting women’s entrepreneurial intention in Malaysia - Leong, Chermyne Kai Shin (2022)
In the 21st century, the number of women that are venturing into their own business is increasing and there is a plethora of factors why women are beginning to expose themselves in the business world. The theory model that was used in this research paper is the Theory of Planned Behaviour that was discussed by Icek Ajzen in 1980 and it started off with the name Theory of Reasoned Action. The theory comprises 3 key elements in it; perceived behavioural control, subjective norms, and attitudes. 5 independent variables including family support, environmental influences, women’s self-independence, entrepreneurial self-efficacy, and entrepreneurial attitude while women’s entrepreneurial intention was categorised as the dependent variable. Quantitative data was gathered through a questionnaire sent to females in Malaysia. A total of 226 women answered the questionnaires and the respondents' data was collected using a 5-point likert scale as a data collection instrument. The result shows that family support, women’s self-independence, environmental influences, and entrepreneurial self-efficacy has a significant positive correlation with women entrepreneurial intention in Malaysia.